2012
DOI: 10.1016/j.physa.2011.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized network design by link survivals and shortcuts

Abstract: One of the challenges for future infrastructures is how to design a network with high efficiency and strong connectivity at low cost. We propose self-organized geographical networks beyond the vulnerable scale-free structure found in many real systems. The networks with spatially concentrated nodes emerge through link survival and path reinforcement on routing flows in a wireless environment with a constant transmission range of a node. In particular, we show that adding some shortcuts induces both the small-w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Second, the complementary added shortcuts improve the robustness. It has already been shown that adding some shortcut links between uniform randomly chosen nodes improves the robustness in the theory for the small-world model [37] and also in the numerical simulations for many networks [10], [15], [16], [38]. The robustness is further improved due to the positive degreedegree correlations in the onion-like network as shown later, however the case of δ = 0 as the uniform random selections does not give the nearly optimal robustness.…”
Section: A Network Modelmentioning
confidence: 78%
See 1 more Smart Citation
“…Second, the complementary added shortcuts improve the robustness. It has already been shown that adding some shortcut links between uniform randomly chosen nodes improves the robustness in the theory for the small-world model [37] and also in the numerical simulations for many networks [10], [15], [16], [38]. The robustness is further improved due to the positive degreedegree correlations in the onion-like network as shown later, however the case of δ = 0 as the uniform random selections does not give the nearly optimal robustness.…”
Section: A Network Modelmentioning
confidence: 78%
“…To make a structure autonomously, movements or interactions of objects (materials or information) are necessary, therefore naturally induce their flows and form a network as the base. There are several fundamental mechanisms: preferential attachment [2], copying [6], [7], survival [9], [10], subdivision (fragmentation) [13], [14], [15], [16], or aggregation [17], for generating networks in the interdisciplinary research fields of physics, biology, sociology, and computer science. They are summarized in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…Strano et al (2012) utilized 200 years of road network evolution data from a large area located in Milan, Italy, and analyzed the relationship between urbanization and evolution of road networks. Hayashi and Meguro (2012) observed that surviving nodes were concentrated in areas with high population. The analysis of such city-level variables is important with respect to policy discussions.…”
Section: Literature Reviewmentioning
confidence: 98%
“…It has already been shown that adding some shortcut links between randomly chosen nodes improves the robustness in the theory for the small-world model [29] and also in the numerical simulations for geographical networks: random Apollonian networks [30], multi-scale quartered networks [31], and link survival networks [7]. In addition, positive degree-degree correlations tend to appear in randomly growing networks [32].…”
Section: Basic Generation Proceduresmentioning
confidence: 99%
“…While other dynamics of information flows, rumor spreading, opinion formation, synchronization, or logistics on a network, is significant for applications in wireless, sensor, mobile communication systems or autonomous transportation systems, in which operation protocols for birth and death of communication or transportation request, routing, avoidance of congestion, task allocation, queuing, awareness of location, monitoring of system's states or conditions, and so on[44], are necessary. We have pointed out the issues of rethinking packet generation according to population, decentralized routing strategy, and link hierarchy among long and short ranges with high and low transfer speeds[45] in the state-of-the-art network technologies.In addition, although several models have been proposed for the coevolution of network formation and opinion spreading[46,47] and for the coupled dynamics with network evolution and packet flows[6,7,48,49,50], they are beyond…”
mentioning
confidence: 99%